Avenida Liberdade: morfologia e estrutura urbana em Bayeux-PB (1960 a 1989) - Belo, Maiara Ateciene dos Santos (2015)
The Liberdade Avenue, located in the city of Bayeux - PB, sets up since its emergence as a routh or path of the connection of the capital (current João Pessoa) to the interior of Paraíba State. The same consolidated as structural axis of urban expasion, especially between the decades from 1960 to 1980. This period is marked by the city's political emancipation and the specific investments that have transformed the land use, with the replacement of residential use by industries and services. The installation of industries fostered by government incentives and greater economic dynamics made this Avenue a central area or a central axis of economic activities. The 1980s is marked by the beginning of the decline of production of the main industries of the city (especially the beneficiation of sisal fiber) and for the flow bypass to the BR 230, decreasing the intensity of the rate of occupation and transformation of that route. The dissertation aims to analyze the changes occurred on Avenue during the decades from 1960 to 1980. To the concretion of the research were performed methodological procedures of the theoretical basis – conceptual, documentary and cartographic research, refers to files and the newspapers, photographic analysis, use of oral history and production of mental maps. Research results reveal among others, the importance of this avenue as the capital connection path for the interior of the State, the traffic intensity, and the accident occurred on Avenue and its characterization as "Death Row"; and the direct influence exerted by this avenue for the entire city.